قرية اطفال - زين شحبري (My University, 2023)
Choosing a location for the Exhibition and Conference Center near the industrial area in the city of Nablus is a smart strategic move for several reasons: 1. Promoting Local Industries : The site facilitates local companies and factories in showcasing their products and achievements with ease. Visitors, both local and international, can get a close look at Palestinian production, enhancing awareness of Palestinian brands and products. 2. Attracting Investments : This location for the Exhibition Center can attract potential investors who visit the exhibitions and conferences. They get a chance to see Palestine's industrial infrastructure and commercial and manufacturing potentials up close, which may encourage investment in the area. 3. Facilitating Logistics and Transportation : Given its proximity to the industrial area, it's easier for companies to transport products and equipment to the Exhibition Center. This reduces transportation costs and makes it easier for exhibitors to participate in the exhibitions. 4. Fostering Industrial Collaboration : The location can encourage cooperation among different companies and local industries. Geographic proximity allows companies 5. to communicate and collaborate more easily, opening the door for new partnerships and joint projects. 6. Boosting Tourism and the Local Economy : The massive complex attracts visitors from within Palestine and abroad, enhancing tourism and supporting the local economy. Events and conferences bring revenue to hotels, restaurants, and other services. In addition to these benefits, the location of the Exhibition and Conference Center can help enhance Palestine's image as a center for innovation and creativity in the region, highlighting its industrial and commercial capabilities on the international stage.